Pengembangan Modul Ajar Mitigasi dan Adaptasi Perubahan Iklim Berbasis EzGCM Pada Mata Pelajaran Muatan Lokal Untuk Siswa SMA/MA - Katmie, Katmie (FKIP Universitas Palangka Raya, 2025)
Climate change has led to rising global temperatures and increasingly intense natural disasters, making it a global challenge that demands a systematic response through education. This article analyzes the strategic role of education in fostering awareness of climate change mitigation and adaptation by integrating relevant content into the Muatan Lokal (local content) curriculum at the senior high school level. Based on a literature review, the study identifies the urgency of climate change education, analyzes the curriculum policy framework, and explores the potential use of digital solutions such as the EzGCM climate simulation model to enhance learning effectiveness. The findings suggest that a multidisciplinary approach—including educational technology, contextual pedagogy, and environmental psychology—can strengthen students' understanding of climate change impacts and encourage active participation in sustainability actions. This article offers recommendations for developing digital-based teaching materials aligned with the principles of the Merdeka Curriculum and local needs.